Open Source Program Offices - Riehle, Dirk (Computer, 2024)
An open source program office is a company organizational unit tasked with managing the use of, contribution to, and leadership of open source projects from the company's perspective. by way of policies, guidance, and education.
CRIS-Team Scopus Importer:2024-12-06